Efforts to Release Unit IV Satintelkam Kamneg to Prevent Conflict Between Pencak Silat Colleges in the Jurisdiction of the Tuban Police - Apriandi, Mochamad Khoiri Panca (Indonesian Journal of Police Studies, 2024)
This research aims to explore the efforts of Unit IV Kamneg Satintelkam to prevent conflicts between pencak silat schools in the jurisdiction of the Tuban Police. Efforts to prevent conflict are carried out by minimizing weaknesses and threats from both internal and external Intelligence Units. Concrete steps include building relationships with units outside the Tuban Regency area, taking an in-depth approach to pencak silat colleges through coaching to form positive mentality and morals in their members, as well as strengthening intelligence patrols and security during college activities. The author uses theories and concepts to analyze problems and research focus in this final assignment. The theory that the author uses is Management Theory which explains through POAC analysis (Planning, Organizing, Actuating, and Controlling), SWOT Analysis Theory (Strength, Weakness, Organizing, and Threat). Meanwhile, the concepts that the author uses are the concept of raising, the concept of effort, and the concept of intelligence and security. The results of the research show that: 1) the efforts to implement fundraising at the Tuban Police are in accordance with the rules governing each element of management. 2) factors that influence the raising consist of internal factors that support the members’ in-depth experience and knowledge in carrying out the raising and external factors that are supported by the community as information assistance even though there are still pencak silat organizations that are difficult to regulate. Synergy between national intelligence agencies is needed to detect potential threats and indications of conflict and build a comprehensive security system. In conclusion, the effort to raise Unit IV Kamneg Satintelkam is a strategic step in maintaining stability and peace between pencak silat schools in the jurisdiction of the Tuban Police.